Influence of aerobic exercise training on cardiovascular and endocrine-inflammatory biomarkers in hypertensive postmenopausal women - Jarrete, Aline P. [UNESP]; Novais, Iane P. [UNESP]; Nunes, Hygor A. [UNESP]; Puga, Guilherme M. [UNESP]; Delbin, Maria A.; Zanesco, Angelina [UNESP] (Elsevier, 2014)
Given that few studies have examined the interaction between endocrine-inflammatory mediators and aerobic exercise training in hypertensive postmenopausal women, the aim of this study was to investigate whether aerobic exercise training (AET) for twenty-four sessions would alter cortisol, leptin and interleukin-1β (IL-1β) levels. To further analyze endothelium function in response to AET, we also examined redox state as well as NO/cGMP pathway in this population. Eighteen hypertensive postmenopausal women finished this study. AET program consisted of 24 sessions in treadmill, 3 times per week, duration of 30 up to 40 min for each session, for 8 weeks at intensity of 100% of the MLSS according to previous incremental test. Heart rate was monitored in all studied time (resting and during exercise sessions). After 48 h of the last exercise session, blood samples were collected for biochemical analyses (levels of cortisol, leptin, IL-1β, nitrite/nitrate (NOx-), cGMP, malondialdehyde (MDA) and asymmetric dimethylarginine (ADMA); superoxide and catalase activity). We also measured systolic and diastolic blood pressure. A significant reduction in body mass was observed. As expected, systolic and diastolic blood pressure values were significantly reduced after AET in hypertensive women. We also found a marked increase in NOx- levels as well as cGMP concentration in trained women, approximately 37.7 and 30.8%, respectively. No changes in cortisol, leptin, ADMA and IL-1β levels were observed after AET. Similarly, MDA levels and catalase activity were not affected by AET. In contrast, a marked increase in SOD activity was found (86.6%). In conclusion, our findings show that aerobic exercise training for twenty-four sessions promoted a significant reduction in blood pressure by activating NO/cGMP pathway as well as by promoting an up-regulation of SOD activity without changing in cortisol/leptin levels in postmenopausal hypertensive women. © 2014 The Authors. Published by Elsevier Inc. All rights reserved.
Keywords: Blood pressure; Cortisol; Leptin; Nitric oxide pathway; Redox state